Clinical profile and predictors of recurrence of first episode of unprovoked seizures in children of the age group 1 month to 12 years - Ambili Susan Jacob; Urmila K.V (Al Ameen Journal of Medical Sciences)
Background: Unprovoked seizures in children, occurring without immediate precipitating factors, pose significant challenges due to their potential to recur. Objectives: This study aims to identify clinical profile and predictors of recurrence in children aged 1 month to 12 years presenting with their first unprovoked seizure. Methods: Conducted over one and a half years in a tertiary care hospital in North Kerala, the study included 61 children. Data on seizure characteristics, past medical history, EEG and neuroimaging findings, and recurrence rates were analysed. Results: It was revealed that there is a 52% recurrence rate, with the highest recurrence occurring within the first 3 months (71.9%). Significant predictors of recurrence included seizures occurring during sleep, a history of neurological insults, developmental delay or intellectual disability, and abnormal EEG or neuroimaging findings. Factors such as age, gender, type of seizure, and status epilepticus did not significantly impact recurrence risk. Conclusions: The study underscores the importance of identifying these predictors for optimizing treatment and monitoring strategies. Close follow-up is recommended for children with identified risk factors to enhance management and improve long-term outcomes.